Experimental dissidence: economies of credibility in drug regulation - McGoey, L (2010)
In 2004, a former FDA medical officer named David Ross watched news coverage of one of the highest-profile pharmaceutical controversies in recent years: Merck’s withdrawal of Vioxx, its bestselling painkiller, from the global marketplace. At the time, David Ross railed to his wife about the actions of David Graham, an associate director of drug safety at the FDA who drew international attention for testifying before the US Senate about the FDA’s handling of Vioxx. Graham said his supervisors ignored warnings that Vioxx could lead to cardiac arrest, and asked him to change his conclusions on an internal report about Vioxx’s risks. Today, David Graham is still at the FDA. David Ross is not. But something both have in common is a concern that FDA has not amended policies much in the wake of the Vioxx controversy, and may be, in some ways, seeking to police internal criticism more strictl